Identification of a miRNA based model to detect prognostic subgroups in patients with aggressive B-cell lymphoma. Issue 5 (16th April 2021) - Nordmo, Carmen; Glehr, Gunther; Altenbuchinger, Michael; Spang, Rainer; Ziepert, Marita; Horn, Heike; Staiger, Annette M.; Ott, German; Schmitz, Norbert; Held, Gerhard; Einsele, Hermann; Topp, Max; et al.
Abstract: In order to differentiate prognostic subgroups of patients with aggressive B-cell lymphoma, we analyzed the expression of 800 miRNAs with the NanoString nCounter human miRNA assay on a cohort of 228 FFPE samples of patients enrolled in the RICOVER-60 and MegaCHOEP trials. We identified significant miRNA signatures for overall survival (OS) and progression-free survival (PFS) by LASSO-penalized linear Cox-regression. High expression levels of miR-130a-3p and miR-423-5p indicate a better prognosis, whereas high levels of miR-374b-5p, miR-590-5p, miR-186-5p, and miR-106b-5p increase patients' risk levels for OS. Regarding PFS high expression of miR-365a-5p in addition to the other two miRNAs improves the prognosis and high levels of miR374a-5p, miR-106b-5p, and miR-590-5p, connects with increased risk and poor prognosis. We identified miRNA signatures to subdivide patients into two different risk groups. These prognostic models may be used in risk stratification in future clinical trials and help making personalized therapy decisions.